Distribution and Antifungal Susceptibility Profile of Oropharyngeal Candida Species Isolated from People Living with HIV in the Era of Universal Test and Treat Policy in Uganda. - Musinguzi, Benson; Turyamuhika, Laban; Mwesigwa, Alex; Nalumaga, Pauline Petra; Kabajulizi, Immaculate; Njovu, Israel Kiiza; Mwebesa, Edson; Luggya, Tonny; Ocheng, Francis; Kateete, David Patrick; Itabangi, Herbert; Mboowa, Gerald; et al. (Kabale University, 2024)
Background: Despite the increased frequency of oropharyngeal candidiasis among people living with human immunodeficiency virus (HIV), its management is no longer effective due to empirical treatment and the emergence of antifungal resistance (AFR). This study sought to investigate the prevalence of oropharyngeal candidiasis and assess the antifungal susceptibility profile of oropharyngeal Candida species isolated from people living with human immunodeficiency virus. Additionally, we evaluated the correlation between oropharyngeal candidiasis and CD4 T cell as well as viral load counts. Methods: A descriptive cross-sectional study was carried out from April to October 2023 in which 384 people living with HIV underwent clinical examination for oral lesions. Oropharyngeal swabs were collected and cultured on Sabouraud Dextrose agar to isolate Candida species identified using the matrix-assisted laser desorption ionization-time of flight mass spectrometry. Additionally, the antifungal susceptibility profile of Candida isolates to six antifungal drugs was determined using the VITEK® (Marcy-l’Étoile, France) compact system. Data on viral load were retrieved from records, and a CD4 T cell count test was performed using Becton Dickinson Biosciences fluorescent antibody cell sorter presto. Results: The prevalence of oropharyngeal candidiasis was 7.6%. Oropharyngeal candidiasis was significantly associated with low CD4 T cell count and high viral load. A total of 35 isolates were obtained out of which Candida albicans comprised 20 (57.1%) while C. tropicalis and Cglabrata comprised 4 (11.4%) each. C. parapsilosis, C. dubliniensis and C. krusei accounted for 2 (5.7%) each. Additionally, 7 (20%) isolates were resistant to fluconazole, 1 (2.9%) to flucytosine and 0.2 (5.7%) isolates were intermediate to caspofungin. However, specific species isolates like C. albicans showed 20% (4/20), C. glabrata 50% (2/4) and C. krusei 50% (1/2) resistance to fluconazole. Additionally, C. krusei showed 50% resistance to flucytosine. Conclusion: The prevalence of oropharyngeal candidiasis (OPC) among people living with HIV was low, and there was a significant association between OPC and CD4 T cell count as well as viral load. C. albicans was the most frequently isolated oropharyngeal Candida species. C. glabrata and C. krusei exhibited the highest AFR among the non-albicans Candida species. The highest resistance was demonstrated to fluconazole.